Purchase Intention through Engagement as Mediation and Brand Equity as Moderation on Social Media Users - Rensia Ester Herdinasari; Renny Christiarini; Erilia Kusumahati (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study aims to further investigate the purchase intention of social media users. The research explores the impact of social presence, psychological distance, trust, engagement, social media marketing, electronic word of mouth, and brand equity on purchase intention. Engagement functions as a mediator, while brand equity plays a moderating role in the relationships studied. Research data was gathered through the distribution of questionnaires to 290 respondents and processed using the SmartPLS 3.0 program. Â The findings indicate that trust, engagement, electronic word of mouth (e-WOM), and brand equity have a significant impact on purchase intention. However, no influence was observed from social presence, psychological distance, and social media marketing. Additionally, the study revealed that there is no mediating effect through engagement, and the moderating effect of brand equity is less than 5%.